2016
DOI: 10.18267/j.pep.540
|View full text |Cite
|
Sign up to set email alerts
|

Company Profitability Before and After IPO. Is it a Windows Dressing or Equity Dilution Effect?

Abstract: This paper relates to the initial public off ering problem and companies' profi tability levels before and after this event. In the presented study, profi tability ratios in the year before initial public off ering increase over the previous year, and then, after the IPO, fall. This confi rms the phenomenon of distorting the level of profi t before the IPO and partially equity dilution after the IPO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
2
15
1
3
Order By: Relevance
“…Yunanto and Daryono (2014) state that the ability of SMEs to generate profits does not experience significant changes after conducting an IPO. Another study was conducted by Pastusiak, Bolek, Malaczewski, & Kacprzyk (2016) which stated that the company's ability to generate profits actually declined after conducting an IPO.…”
Section: Introductionmentioning
confidence: 99%
“…Yunanto and Daryono (2014) state that the ability of SMEs to generate profits does not experience significant changes after conducting an IPO. Another study was conducted by Pastusiak, Bolek, Malaczewski, & Kacprzyk (2016) which stated that the company's ability to generate profits actually declined after conducting an IPO.…”
Section: Introductionmentioning
confidence: 99%
“…The years 2004 -2014 were quite encouraging for Indonesia's economic performance due to leaving the low-income zone. During this period Indonesia's average economic growth reached 5.8% higher compared to Malaysia and Thailand by only 5.0% and 3.9% [1]. But in 2014 -2018 decreased and relatively stable.…”
Section: Introductionmentioning
confidence: 85%
“…According Pastusiak [1] companies that have registered as Initial Public Offering (IPO) will experience a share price decline in the first three years. Even after the IPO, the results have declined compared to before the tIPO-1 period.…”
Section: Introductionmentioning
confidence: 99%
“…However, research shows that an increasing number of IPO firms under-perform in the years after going public (Jin et al 2017;Pastusiak et al 2016;Mikkelson et al 1997); this phenomenon also exists in the Chinese stock markets (Gao et al 2021;Gui and Lai 2005), which is what stimulated our research interest. Gao et al (2021), based on the data from the Growth Enterprise Market of China (GEMC), showed that IPO firms have no contributions to income-and profit-related performance because the majority of these IPO firms are unable to spend IPO capital on operating performance.…”
Section: Introductionmentioning
confidence: 93%